A Synergetic Codoping Strategy Enabling Performance Improvement of Pure‐Blue Perovskite Quantum Dots Light‐Emitting Diodes. Issue 9 (17th March 2022) - Pan, Jiangyong; Zhao, Zihan; Fang, Fan; Wang, Lixi; Wang, Guangzhao; Liu, Chengjun; Huang, Qianqian; Sun, Jinyi; Huang, Yuling; Mao, Lei; Xie, Jing; Xue, Ying; et al.
Abstract: Highly efficient green and red perovskite quantum dots (PeQDs) light‐emitting diodes (PeQDLEDs) have been achieved. However, blue PeQDLEDs, especially those with the relatively short wavelengths (<470 nm) meeting National Television System Committee blue standard, have struggled to match the high efficiency and stability of their red and green counterparts. The main critical problems are the low photoluminescence quantum yield (PLQY) and poor stability of PeQDs, as well as the unfavorable device structure. Herein, a strategy of codoping Mn 2+ and Ni 2+ in CsPb(Br1.8 Cl1.2 ) is developed to improve the PLQY and thermal stability of PeQDs due to the defect passivation and enhanced formation energy. Meanwhile, the valence band position of PeQDs is elevated to reduce the hole injection barrier benefitting from the synergetic codoping strategy. As a result, the PeQDLEDs based on codoped PeQDs exhibit the maximum external quantum efficiency (EQE) of 3.31% with the emission peak located at 469 nm, and lifetime exceeding 8 min. The work provides a new avenue to achieve efficient and stable pure blue PeQDLEDs. Abstract : A strategy of codoping Mn 2+ and Ni 2+ in CsPb(Br/Cl)3 is developed to improve the photoluminescence quantum yield and thermal stability of perovskite quantum dots (PeQDs) due to the defect passivation and enhanced formation energy. The resulting PeQD light‐emitting diodes exhibit the maximum external quantum efficiency of 3.31% with the emission peak located at 469 nm, and lifetime exceeding 8 min.